Strictly Concave Parametric Programming, Part II: Additional Theory and Computational Considerations - Geoffrion, Arthur M. (Management Science, 1967)
The theory presented in Part I of this paper led to a Basic Parametric Procedure for a broad class of strictly concave parametric programs. In this part, additional theory is developed that facilitates efficient computational implementation. An illustrative graphical example is given, and some extensions are indicated.